Ownership Concentration, Firm Size & Agency Cost: Empirical Evidence In Indonesia - Nugrahaningtyas, Andien; Nuraina, Elva; Sulistyowati, Nur Wahyuning (Assets: Jurnal Akuntansi dan Pendidikan, 2025)
This study aims to provide empirical evidence of the influence of ownership concentration on agency costs, as well as to examine the moderating effect of company size. The research method employed is a quantitative approach, utilizing data sources from annual reports. The research sample consists of companies listed on the Indonesian Stock Exchange for the period from 2018 to 2022. Based on purposive sampling, 750 firm years were obtained. Using OLS and Moderated Regression Analysis (MRA), the results of this study show that the concentration of ownership has a positive effect on agency costs. The size of the company also weakens the relationship between the concentration of ownership and the agency's price. Keywords : Agency Costs; Ownership Concentration; Firm Size; Agency Problem